2013
DOI: 10.1080/13583883.2013.790071
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Shape of University Decision-Making Processes and the Consequences for Faculty Participation in Ireland

Abstract: For faculty, the idea of collegial and participative decision-making has been one of the central values of academic life. Yet, despite evidence that universities in Ireland have experienced considerable institutional change in recent years, there remains a considerable dearth of research on its consequences for faculty participation in governance and decision-making processes. A case study of the School of Business at University College Dublin (UCD) is used to illustrate how a programme of large-scale institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Academic staff members will work hard if they feel they are contributing and appreciated for their contribution by their administrators (Johnsrud & Rosser, ). Dowling‐Hetherington () suggests that participative decision‐making should be one of the central values of academic life. Similarly, Bryman () points out that effective leaders at department level should set a clear vision, communicate well, be trustworthy and considerate, and allow the academic staff to participate in key decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Academic staff members will work hard if they feel they are contributing and appreciated for their contribution by their administrators (Johnsrud & Rosser, ). Dowling‐Hetherington () suggests that participative decision‐making should be one of the central values of academic life. Similarly, Bryman () points out that effective leaders at department level should set a clear vision, communicate well, be trustworthy and considerate, and allow the academic staff to participate in key decisions.…”
Section: Resultsmentioning
confidence: 99%
“…exerted on the professoriate and how individual faculty members react in their professional pursuits (Höhle & Teichler, 2013;Locke & Teichler, 2007). Faculty across Europe, in no small measure due to the Bologna Process, increasing administrative demands, and expanded teaching responsibilities, are experiencing more negative impacts on their work from the rise of managerialism (Dowling-Hetherington, 2013;Locke et al, 2011;Teelken, 2011). With dramatic geopolitical shifts toward less free inquiry (e.g.…”
Section: Research Questionsmentioning
confidence: 99%
“…Multiple authors have suggested that distributed leadership may reduce the tension and differences between faculty governance and formal, hierarchical leadership models in colleges and universities (Jones, Lefoe, Harvey, & Ryland, ). Dowling‐Hetherington () suggested that a more distributed leadership model has the potential to reengage disillusioned faculty who disconnected from governance and organizational life because of a more executive‐style management and decision‐making. Jones et al () found in a study of Australian universities that a distributed leadership model with a high degree of collaboration across professional staff and academics supported successful pedagogy reform.…”
Section: Conceptual Frameworkmentioning
confidence: 99%